The palaeobiogeographical spread of the acritarch Veryhachium in the Early and Middle Ordovician and its impact on biostratigraphical applications - Servais, Thomas; Li, Jun; Molyneux, Stewart G.; Rubinstein, Claudia Viviana; Vecoli, Marco; Yan, Kui (GFF)
The genus Veryhachium Deunff, 1954, is one of the most frequently documented acritarch genera, being recorded from the Early Ordovician to the Neogene. Detailed investigations show that Veryhachium species first appeared near the South Pole in the earliest part of the Tremadocian (Early Ordovician). The genus was present at high palaeolatitudes (generally>60° S) on the Gondwanan margin during the Tremadocian before spreading to lower palaeolatitudes on the Gondwanan margin and other palaeocontinents (Avalonia and Baltica) during the Floian. It became cosmopolitan in the Middle and Late Ordovician. Although useful for distinguishing Ordovician from Cambrian strata, the diachronous first appearance data of Veryhachium morphotypes mean that they should be used with caution for long-distance correlation. Fil: Servais, Thomas. Centre National de la Recherche Scientifique; Francia. Université Lille 1; Francia Fil: Li, Jun. Chinese Academy of Sciences; República de China Fil: Molyneux, Stewart G. British Geological Survey; Reino Unido Fil: Rubinstein, Claudia Viviana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina Fil: Vecoli, Marco. Université Lille 1; Francia. Saudi Aramco. Biostratigraphy Group. Geological Technical Services Division; Arabia Saudita. Centre National de la Recherche Scientifique; Francia Fil: Yan, Kui. Chinese Academy of Sciences; República de China. State Key Laboratory of Palaeobiology and Stratigraphy; China